1964
DOI: 10.3181/00379727-117-29685
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Deficiency and Hepatic DNA Synthesis.

Abstract: FOLATE AND DNA SYNTHESIShold true when stimuli other than endotoxin are used to produce EP. Third, the semiquantitative data obtained by testing EPor any other substance employed in pyrogen assays-improves the accuracy of these assays and yields more meaningful information for comparison of different pyrogenic substances. Fourth, providing it is clearly defined, the concept of the minimum pyrogenic dose is useful in standardizing the pyrogenic response, and to compare data from different laboratories.It should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1965
1965
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…These results are in agreement with studies by Leevy et a/. (24) which indicated that deficiencies of folate, vitamin BI2, and vitamin B6 diminished DNA synthesis whereas deficiencies of thiamin, riboflavin, nicotinic acid, pantothenic acid, and biotin did not impair DNA synthesis in the liver (5). There was no significant change in total RNA, protein content, and amylase content or amylase secretion.…”
supporting
confidence: 94%
“…These results are in agreement with studies by Leevy et a/. (24) which indicated that deficiencies of folate, vitamin BI2, and vitamin B6 diminished DNA synthesis whereas deficiencies of thiamin, riboflavin, nicotinic acid, pantothenic acid, and biotin did not impair DNA synthesis in the liver (5). There was no significant change in total RNA, protein content, and amylase content or amylase secretion.…”
supporting
confidence: 94%
“…After these sequential events have been com pleted, it is believed that DNA synthesis in hepatocytes reaches a peak around 1d after PH, and then substan tial cell proliferation begins. Within 3-14d, organ weight has been shown to be restored to the original mass (12)(13)(14). In this experiment, in spite of the slight liver enlargement at the time of PH, liver weight for the CLA fed group was significantly lower than control rats at 7-d post PH.…”
Section: -D Post Phmentioning
confidence: 56%